Radiation protection for procedures performed outside the Radiology Department : recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2000)
Annotation Provides practical recommendations on how to protect workers while performing X-ray procedures outside the radiology department. Coverage includes radiologic examinations in the cardiac catheterization laboratory and in the operating room, sources of exposure to workers, personal monitoring, and administrative responsibilities. There is no coverage of exposures from nuclear medicine or radiation therapy. Appendices overview the nature of the biological effects of ionizing radiation and discuss basic medical imaging. Includes a glossary. Useful for clinical staff who conduct medical procedures, radiation protection staff, and those responsible for developing employee education and training programs. Annotation copyrighted by Book News Inc., Portland, OR.
"Issued August 31, 2000."
Keywords: Radiation -- Safety measures.; Diagnosis, Radioscopic -- Evaluation.; elektronické knihy; electronic books